The Empathy and Attitudes towards an Economic System and Social Issues - Czerniawska, Mirosława (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The main aim of this research is the investigation of attitudes towards an economic system and social issues. It was assumed that these attitudes depend on a personality trait of empathy. The study group consisted of 325 students. The Empathic Understanding of Others Questionnaire (Węgliński) was used. The attitudes were diagnosed on the basis of the set of views (four pairs of statements from W. Morawski and the publication edited by J. Reykowski). The results of the research show that people with the higher empathy index support state regulations of labour market and the reduction of unemployment. They also present more egalitarian attitude and find the welfare state a necessity.